2023
DOI: 10.3390/plants12030549
|View full text |Cite
|
Sign up to set email alerts
|

Edible Halophytes and Halo-Tolerant Species in Apulia Region (Southeastern Italy): Biogeography, Traditional Food Use and Potential Sustainable Crops

Abstract: The Mediterranean basin is rich in wild edible species which have been used for food and medicinal purposes by humans throughout the centuries. Many of these species can be found near coastal areas and usually grow under saline conditions, while others can adapt in various harsh conditions including high salinity. Many of these species have a long history of gathering from the wild as a source of food. The aim of this contribution is an overview on the most important halophyte species (Salicornia sp. pl., Arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 160 publications
0
31
0
Order By: Relevance
“…In nature, many species of perennial shrubs reproduce agamically by rooting their lower stems. This portion can be separated from the plant and used for vegetative multiplication [ 72 ]. In fact, there exists research in which fragments of A. macrostachyum are used, such as that of Paraskevopoulou et al [ 73 ], who described that cuttings of this species can be used for green roof systems in arid areas.…”
Section: Discussionmentioning
confidence: 99%
“…In nature, many species of perennial shrubs reproduce agamically by rooting their lower stems. This portion can be separated from the plant and used for vegetative multiplication [ 72 ]. In fact, there exists research in which fragments of A. macrostachyum are used, such as that of Paraskevopoulou et al [ 73 ], who described that cuttings of this species can be used for green roof systems in arid areas.…”
Section: Discussionmentioning
confidence: 99%
“…Developing and strengthening conservation genetic studies to assess or protect genetic diversity has been wildly suggested as a good strategy to assure the sustainable use of wild resources, especially endangered plants ( Liu et al., 2020 ; Garcia-Jacas et al., 2021 ; Accogli et al., 2023 ; Perrino et al., 2023 ). The precise evaluations of genetic diversity and population genetic structure could assist to compile knowledge-based and efficient protection programs ( Liu et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diverse genetic resources are essential for crop improvement ( Maxted et al., 2008 ; Maxted and Kell, 2009 ; Perrino and Wagensommer, 2021 ; Perrino and Wagensommer, 2022 ; Accogli et al., 2023 ). The region, in spite of having potential genetic diversity in the landraces of Capsicum spp., is yet to be efficiently utilized.…”
Section: Introductionmentioning
confidence: 99%